Professional competences for the development of multipotential abilities of future teachers in university training - A. M. Garifullina (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. Multipotency is interpreted as multiple human capabilities in various fields and spheres of life. In general, the little-studied concept is of particular importance today. As a result of the globalization, more and more often people go through multiple stages in self-determination and the formation of their «I». The distribution of goals and objectives in the process of developing the multipotential abilities of future teachers makes it possible to determine the most important stages in the activities of teachers of educational organizations at its various stages. We consider national and foreign research in the field of multipotency, affecting the «self» of a person: self-determination, self-actualization and self-realization.Goal. The goal is to study professionally signifycant competences for the development of multipotential abilities of future teachers in university training.Materials and methods. The method of statistical analysis, critical thinking, inversion method, questionnaires and interviews allowed the author to investigate undergraduate and graduate students of the Instituteof Psychology and Education, KFU, for multipotentiality.Results and discussion. In the process of the study, we obtained interesting results that there are more students who are confident in the chosen profession at the bachelor degree than the ones in the master degree program. This result allowed us to conclude that the younger the age of the respondents, the more confident they are in the chosen development trajectory. Among master students there were more students that were doubtful. According to the majority of respondents-masters, this is due to the fact that the acquired experience prevents to be objective in the process of self-realization of multipotential abilities.Conclusion. Multipotentiality is an excellent tool in the process of personality development. A student who has chosen a certain profile can transform their knowledge from the so-called hard skills to soft skills that can be re-trained/adjusted to something more progressive and relevant for the current period of time).